La delincuencia y su efecto en los resultados financieros de los centros de diversión nocturna turísticos de la ciudad de Riobamba, período 2022-2024 - Villacis Vivero, Juan Alfredo (2026)
This research analyzes the impact of rising crime on the financial performance of tourist-oriented nighttime entertainment venues in the city of Riobamba during the 2022–2024 period. The increase in thefts, assaults, extortions, fights, drug micro-trafficking, and public disorder has weakened the perception of safety in high-traffic areas, directly affecting customer turnout and the city’s tourism image. To better understand this phenomenon, a mixed-methods approach was applied, combining qualitative and quantitative techniques supported by surveys administered to 16 nightlife establishments, direct observation, and documentary analysis of financial reports. The financial analysis revealed an average operating profit of 7.8%, reflecting a level of profitability that is vulnerable to fluctuations in sales or increases in costs. Additionally, business perceptions indicate strong dissatisfaction with the effectiveness of local authorities in controlling crime in nighttime tourism areas. The study concludes that crime directly affects the profitability and economic sustainability of Riobamba’s tourist nightlife venues, compromising their market continuity and the competitiveness of local nighttime tourism. Mitigation strategies are proposed based on improving citizen security, technological investment, public-private coordination, and strengthening financial management.